Evaluation of the effect of cervical spine bone distribution on fixation in ankylosing spondylitis - Wang, Beiyang; Tang, Jian; Wang, Zhiqiang; Deng, Chen; Lv, Junqiao; Gao, Fang; Xiong, Xiaoyan; Sun, Lin (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeThe distribution of cervical bones in ankylosing spondylitis (AS) differs from that of the normal cervical spine. Traditional simulation methods often yield inaccurate results in finite element analysis. The current study aimed to construct ankylosing spondylitis cervical spine fracture (ASCF) models based on Hounsfield Unit (HU) values to analyze the effects of different fixation approaches.MethodsQuantitative HU measurements of cervical vertebrae and lateral masses were obtained from CT scans of 20 patients with AS. A finite element model of ASCF was constructed based on HU values and was compared with a traditional ASCF model from multiple perspectives. Additionally, three ASCF models were used to compare the effects of various fixation approaches. A meta-analysis of screw loosening rates was conducted to further validate the efficacy of the models.ResultsThe HU value of the cervical lateral mass in AS is higher than the corresponding mass in the vertebral body. Finite element analysis results indicated that the anterior approach is less stable compared to other approaches, as evidenced by the maximum stress (MS) value of the screw and the maximum displacement (MD) of the entire model. These findings were corroborated by the meta-analysis of screw loosening rates in ASCF.ConclusionASCF exhibits an uneven distribution of cervical bone, with more severe osteoporosis in the anterior cervical spine. Consequently, simple anterior approaches to fixation may lead to screw loosening in ASCF.